Student teachers’ perception of their teaching competency assessed by a framework for assessing student teachers’ english teaching competency (fastetc) - Thao, Tran Quoc (H. : ĐHQGHN, 2020)
Training teachers to meet the professional standards is one of the top missions prioritized by teacher training institutions. Nevertheless, how student-teachers’ teaching competency is assessed is considered as one of the highest concerns by teacher trainers and educators. This study, therefore, aims at examining student teachers’ perception of their teaching competency assessed by a framework for assessing student teachers’ English teaching competency (FASTETC) in the TESOL methodology course at a Ho Chi Minh City-based university, Vietnam. The study involved 85 student teachers majoring in TESOL methodology in answering a self-evaluation questionnaire. The results indicated that the research participants realized they could meet the course outcomes and professional standards in terms of attitudes, knowledge and skills of English teaching methodology (ETM) and English language proficiency. Furthermore, student teachers were aware that their knowledge and skills of ETM outperformed their attitudes of ETM. Such preliminary results can encourage the use of a teaching competency framework for assessing and assuring the quality of student teachers’ teaching competency in similar contexts.